Tobacco Rotated with Rapeseed for Soil-Borne Phytophthora Pathogen Biocontrol: Mediated by Rapeseed Root Exudates - Fang, Yuting; Zhang, Limeng; Jiao, Yongge; Liao, Jingjing; Luo, Lifen; Ji, Sigui; Li, Jiangzhou; Dai, Kuai; Zhu, Shusheng; Yang, Min (Frontiers in Microbiology, 2016)
Black shank, caused by Phytophthora parasitica var. nicotianae, is a widespread and destructive disease of tobacco. Crop rotation is essential in controlling black shank. Here, we confirmed that rotating black shank-infested fields with rapeseed (Brassica napus) suppressed the incidence this disease. Further study demonstrated that rapeseed roots have a strong ability to attract zoospores and subsequently stop the swimming of zoospores into cystospores. Then, rapeseed roots secrete a series of antimicrobial compounds, including 2-butenoic acid, benzothiazole, 2-(methylthio)benzothiazole, 1-(4-ethlphenyl)-ethanone, and 4-methoxyindole, to inhibit the cystospore germination and mycelial growth of P. nicotianae. Thus, rapeseed rotated with tobacco suppresses tobacco black shank disease through the chemical weapons secreted by rapeseed roots.